2021
DOI: 10.11646/phytotaxa.487.1.2
|View full text |Cite
|
Sign up to set email alerts
|

<strong><em>Cyathea</em> Sm. (Cyatheaceae) on Trindade Island (Brazil): An integrative approach</strong>

Abstract: Trindade is a Brazilian oceanic island approximately 1,100 km from the American mainland. The Cyathea Sm. plants from Trindade were originally considered an endemic species, Cyathea copelandii Kuhn & Luerssen, but later included in Cyathea delgadii Sternb. Based on molecular data (trnL-trnF, trnG-trnR and rbcL-accD), morphometric analysis of leaf characters, scanning electron microscopy of indusia and spores, and habitat suitability modeling, the present study confirms the status of C. copelandii as a syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…previously considered to be endemic, was proved to belong to the broadly distributed C. delgadii Sternb. (Faria et al, 2021). Lücking, M. Cáceres, N.G.…”
Section: Discussionmentioning
confidence: 99%
“…previously considered to be endemic, was proved to belong to the broadly distributed C. delgadii Sternb. (Faria et al, 2021). Lücking, M. Cáceres, N.G.…”
Section: Discussionmentioning
confidence: 99%
“…Muñoz et al (2004) showed the importance of air currents as an LDD mechanism in the Southern Hemisphere for non‐flowering plant species distributions, demonstrating a pattern of diaspore transfer from South America towards Africa at mid latitudes. More recently, the application of newly available molecular tools to samples obtained on the mid‐Atlantic Trindade Island (Câmara, Menezes, et al, 2022; Faria et al, 2021) has corroborated this hypothesis. Older Antarctic studies based on macroscopic observations of air, snow and moss carpets (e.g.…”
Section: Introductionmentioning
confidence: 91%